2016
DOI: 10.1111/eea.12497
|View full text |Cite
|
Sign up to set email alerts
|

Physiological development and dispersal ability of newly emerged Monochamus galloprovincialis

Abstract: Novel associations between exotic pathogens and native insects may result in major ecological and economical losses. In Europe, Monochamus galloprovincialis (Olivier) (Coleoptera: Cerambycidae) is the only known vector of the exotic pine wood nematode Bursaphelenchus xylophilus (Steiner & Buhrer) Nickle (Nematoda: Aphelenchoididae), the causal agent of pine wilt disease (PWD). Transportation of goods containing nematode-infested beetles is the main pathway for the spread of the disease. In this scenario, manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Rassati et al (2012) reported that funnel traps baited with the same components of Galloprotect Pack are effective at low densities of Monochamus and can therefore be used as a general tool for beetle surveillance at ports of entry and forests, but also recommend that tree health assessments and trapping should be conducted outside of port areas as well (Rassati et al 2014). A constraint of this trap/lure combination is that newly emerged Monochamus adults require a sexual maturation feeding period, during which they are not attracted to the pheromones, kairomones, or host volatiles included in the Galloprotect Pack (Álvarez et al 2016), and during which they are able to disperse at least 2 km from the point of emergence (Sanchez-Husillos et al 2016). Identification and isolation of volatiles attractive to immature Monochamus adults should be a focus for the development of a truly comprehensive lure.…”
Section: Resultsmentioning
confidence: 99%
“…Rassati et al (2012) reported that funnel traps baited with the same components of Galloprotect Pack are effective at low densities of Monochamus and can therefore be used as a general tool for beetle surveillance at ports of entry and forests, but also recommend that tree health assessments and trapping should be conducted outside of port areas as well (Rassati et al 2014). A constraint of this trap/lure combination is that newly emerged Monochamus adults require a sexual maturation feeding period, during which they are not attracted to the pheromones, kairomones, or host volatiles included in the Galloprotect Pack (Álvarez et al 2016), and during which they are able to disperse at least 2 km from the point of emergence (Sanchez-Husillos et al 2016). Identification and isolation of volatiles attractive to immature Monochamus adults should be a focus for the development of a truly comprehensive lure.…”
Section: Resultsmentioning
confidence: 99%